Contribution to the fall stonefly (Plecoptera) fauna of Korea - Murányi, Dávid (Illiesia, 2011)
The Plecoptera material collected during a fall visit to the Republic of Koreawas studied. Nemoura aquila Murányi sp. n. is described from both sexes. The unknown female of Despaxia asiatica Zwick and the unknown larva of Nemourageei Wu are described. The male and the larva of Protonemura villosa Ham & Lee are redescribed and the female is described for the first time, and the species is transferred to the P. towadensis group sensu Shimizu. The internal female genital sclerites of Amphinemura steinmanni Zwick are also described.
Keywords: Amphinemura; entomology; Plecoptera; Protonemura; Nemoura; new species; Despaxia; description; Korea; entomologija; vrbnice; nove vrste; Koreja